Awareness on Cancer and Barriers to Health Care Seeking Among Adults of Bardiya - Sah, Chanda; Aryal, Srijana; Neupane, Gita (Journal of Universal College of Medical Sciences, 2020)
INTRODUCTION: Cancer is a leading public health problem worldwide. Low awareness on cancer leads to increase in burden of cancer diagnosis and treatment. MATERIAL AND METHODS: Descriptive cross-sectional study was conducted to find out awareness regarding cancer among people. Total 100 samples were selected by using non-probability purposive sampling method. Semi-structured interview schedule was developed with the guide of the Cancer Awareness Measure (CAM) to collect data. Collected data were analysed by using descriptive and inferential statistics. RESULTS: The findings of the study showed that none of the study respondents were aware of all the nine warning signs of cancer. Majority (80%) of the respondents were aware that “a sore that doesn’t heal” and minority (15%) knew about “change in bowel and bladder habit” as warning signs of cancer. Regarding risk factors, majority knew chemical fertilizer and pesticides and unseasonal fruits and vegetables (90%), smoking (88%) as risk factors of cancer and minority (32%) knew about excessive sun exposure. There was statistically significant association between respondents’ level of awareness regarding cancer with education status (p= 0.011). CONCLUSION: Findings of the study revealed that more than half (68%) of the adults had low awareness regarding cancer. Emotional barriers (88%) were known to be affecting health care seeking behaviours for cancer. Therefore, it is recommended to organize health awareness campaigns addressing emotional barriers might improve in early diagnosis and treatment of cancer.